Taking Stock: EU Common Commercial Policy in the Lisbon Era - David Kleimann (Aussenwirtschaft, 2011)
The first 16 months of the EU's common commercial policy (CCP) in the post-Lisbon period provide indicative insights into how the European Parliament, the European Commission and the Council ofMinisters interpret their respective roles under the new legal framework introduced by the Lisbon Treaty. This paper analyses the amendments, the institutional capacities to respond to the reform challenges and the evolving institutional balance applying to Lisbon-era common commercial policy.Against this backdrop, the paper gives an overview of the changing dynamics of EU trade and investment policy in a context of enhanced politicization resulting from the European Parliament's involvement in the decision- making process.Particular importance is given to the question whether enhanced EP involvement in decision-making has the potential to lead to a scenario resembling the policy process in the United States, where congressional responsibility for trade and investment policy has resulted in the capture of the policy agenda by special interest groups and snail-paced policy progress (if any) in recent years.Accordingly, the paper scrutinizes the political preferences that the European Parliament is introducing into current European trade policy debates as well as the framework legislation and trade agreements. Finally, it is argued that parliamentary involvement in making common commercial policy has the potential to narrow the gap between European public political preferences and perceptions, on the one hand, and actual EU trade policies on the other, and to place EU trade and investment policies on a foundation of renewed public political support. In the author's view, however, it is imperative that such an achievement is based on well-informed, responsible, sustainable and clearly communicated policy proposals from the MEPs, who respond to and seek to balance the multiplicity of interests of CCP stakeholders in European civil society and respect the Union's international obligations.
Keywords: F13; 330; Common commercial policy; European Union; European Parliament; Lisbon Treaty; Trade; Investment and external action